Analyses of Methylomes Derived from Meso-American Common Bean (Phaseolus vulgaris L.) Using MeDIP-Seq and Whole Genome Sodium Bisulfite-Sequencing - Crampton, Mollee; Sripathi, Venkateswara R.; Hossain, Khwaja; Kalavacharla, Venu (Frontiers in Plant Science, 2016)
Common bean (Phaseolus vulgaris L.) is economically important for its high protein, fiber, and micronutrient contents, with a relatively small genome size of ~587 Mb. Common bean is genetically diverse with two major gene pools, Meso-American and Andean. The phenotypic variability within the genotypes is partly attributed to the genetic diversity and epigenetic changes that are largely influenced by environmental factors. It is well established that an important epigenetic regulator of gene expression is DNA methylation. Here, we present results generated from two high-throughput sequencing technologies, methylated DNA immunoprecipitation-sequencing (MeDIP-seq) and whole genome bisulfite-sequencing (BS-Seq). Our analyses revealed that common bean displays similar methylation patterns as other previously published plant methylomes, with CG ~50%, CHG ~30%, and CHH ~2.7% methylation, however, these differ from the common bean reference methylome of Andean origin. We identified higher CG methylation levels in both promoter and genic regions than CHG and CHH contexts. Moreover, we found relatively higher CG methylation levels in genes than in promoters. Conversely, the CHG and CHH methylation levels were highest in promoters than in genes. This is the first genome-wide DNA methylation profiling study in a Meso-American common bean cultivar (“Sierra”) using NGS approaches. Our long-term goal is to generate genome-wide epigenomic maps in common bean focusing on chromatin accessibility, histone modifications, and DNA methylation.